BETWEEN SPEECH AND WRITING: LINGUISTIC-RHETORICAL ANALYSIS OF THE WORDPLAYING GENRE IN THE NORTHEASTERN CANTORIA DE VIOLA IN BRAZIL - do Nascimento, Antonio Marinho; Bezerra, Benedito Gomes (Seven Editora, 2026)
The Brazilian northeastern cantoria de viola, orally improvised but often recorded in writing, has aroused the interest of many scholars, from different perspectives, from literary and cultural studies to musical and sociological approaches. Few studies, however, have been conducted from a strictly linguistic perspective. In this article, our aim was to conduct an exploratory study of the wordplaying genre in the cantoria de viola under the perspective of the Language for Specific Purposes, based on the theoretical and methodological contribution of Genre Analysis (Swales, 1990). Methodologically, the study consisted of applying move analysis to a corpus of twenty stanzas of sextilhas, a typical genre of the cantoria de viola, authored by Louro do Pajeú, focusing on the use of wordplaying by the poet. As a result, rhetorical moves were found that are both typical of the universe of the cantoria and specific to the poet’s poetics. These moves are more general, relating to the aspects of introduction, development and conclusion of the text in any genre, as well as specific moves in the world of oral literature, which lead to its aesthetic prism and its playful context. Such results may contribute to shedding more light on the genre of cantoria and on Louro’s creative work, including highlighting the non-formal literacies typical of the activities of viola singers. DOI: https://doi.org/10.56238/sevened2026.008-121